STRATEGI PENINGKATAN MORAL PESERTA DIDIK DALAM PERSPEKTIF PENDIDIKAN ISLAM: KAJIAN LITERATUR - Ahmad Mulyono (Irfani, 2025)
This article discusses strategies for enhancing students' moral character as an effort to address the challenge of moral degradation among students and society, triggered by the weakening of religious adherence, inadequate moral guidance from families, schools, and communities, the strong influence of materialistic–hedonistic–secularistic culture, and the government's low commitment. This study employs a qualitative method with a literature review approach to analyze the concepts of morality and ethics from an Islamic education perspective and formulate effective strategies. The findings indicate that moral development must consider three elements according to Lickona—moral understanding, moral feeling, and moral action—integrated with faith as the foundation. The recommended strategies include exemplary behavior, education, and religious outreach (dakwah), implemented through separate subject models, integrated learning, extracurricular activities, a combined model, school culture reinforcement, and collaboration with all stakeholders. A well-planned and collaborative effort is believed to foster a an intellectually intelligent and a noble generation. Keywords: morality, ethics, Islamic education, strategy, students